2020
DOI: 10.1542/peds.2020-0146
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Preterm Heart From Birth to Young Adulthood: A Meta-analysis

Abstract: CONTEXT: Preterm birth is associated with incident heart failure in children and young adults.OBJECTIVE: To determine the effect size of preterm birth on cardiac remodeling from birth to young adulthood.DATA SOURCES: Data sources include Medline, Embase, Scopus, Cochrane databases, and clinical trial registries (inception to March 25, 2020).STUDY SELECTION: Studies in which cardiac phenotype was compared between preterm individuals born at ,37 weeks' gestation and age-matched term controls were included.DATA E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 72 publications
9
77
0
7
Order By: Relevance
“…The two authors of this paper independently assessed the methodological quality of included studies, using a 10-item modified scoring system to reflect favourable design, reporting, as well as attrition and compliance (Supplementary Table 2). (18)(19)(20) For each item, a score of 1 was allocated if the study met the criteria for that subcategory. Attrition and compliance criteria were based on standard guidelines for exercise intervention trials.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The two authors of this paper independently assessed the methodological quality of included studies, using a 10-item modified scoring system to reflect favourable design, reporting, as well as attrition and compliance (Supplementary Table 2). (18)(19)(20) For each item, a score of 1 was allocated if the study met the criteria for that subcategory. Attrition and compliance criteria were based on standard guidelines for exercise intervention trials.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…LBW has been consistently associated with increased adult cardiovascular mortality, hypertension, metabolic syndrome, diabetes and lung morbidity. 10,11,12,[15][16][17][18][19][20][21] LBW can be a result of being born too small -fetal growth restriction-and/or too early -prematurity-.…”
Section: Interpretation Of Novel Findingsmentioning
confidence: 99%
“…(which was not certified by peer review) preprint prematurity, key developmental stages have to take place ex utero in non-physiological conditions 39 leading to cardiovascular hypertrophy and impaired lung development, insulin sensitivity and bone density. [20][21][22]39…”
Section: Interpretation Of Novel Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 The unique cardiac phenotype of premature infants is known to persist into childhood as a recent meta-analysis demonstrated that preterm-born individuals have persistently smaller ventricular dimensions, ongoing systolic and diastolic dysfunction that worsens with age, and an accelerated rate of LV hypertrophy from childhood to adulthood. 8 Our group has explored the natural progression of rotational mechanics in preterm infants immediately after birth, 1 but the interpretation of the results has been lacking without serial comparisons to term infants.…”
Section: Introductionmentioning
confidence: 99%